Correction of the single breath carbon monoxide transfer factor in exercise for variations in alveolar oxygen pressure. - Kendrick, A. H. (1994)
BACKGROUND--Carbon monoxide transfer factor (TLCO) varies inversely with the partial pressure of alveolar oxygen (PAO2). During exercise the PAO2 in the alveolar gas sample bag decreases so the TLCO increases more than would be expected from the effects of exercise alone. The effects of PAO2 on the estimation of TLCO during exercise have been investigated and studies have been performed to determine whether it is appropriate to standardise to a PAO2 of 16 kPa. METHODS--TLCO was estimated at rest and at a single level of exercise in six normal subjects using test gas mixtures of 0.3% carbon monoxide, 14% helium, and oxygen in three different percentages (17%, 21%, and 27%), remainder nitrogen. In three of the subjects an incremental exercise test with estimates of oxygen consumption (VO2) and cardiac frequency (fC) was also performed using a mixture containing 18% oxygen. RESULTS--TLCO decreased as levels of inspired oxygen increased. When standardised to a PAO2 of 16 kPa TLCO became independent of the inspired oxygen concentration. The significance of the curvilinear relations of TLCO and transfer coefficient to VO2 and fC improved. CONCLUSION--The single breath breath holding TLCO should be standardised to a PAO2 of 16 kPa when estimated during exercise.